Ex Libris A. Golubiew / GA. - Achrem-Achremowicz, Gracjan (1899-1942) ([wydawca nieznany], 1935)
Przedstawia dwóch mężczyzn stojących na ulicy pod latarnią. Napis u góry: Ex Libris, u dołu: A. Golubiew.